2016
DOI: 10.3390/proteomes4030027
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Skeletal Muscle Proteomics Using Two-Dimensional Gel Electrophoresis

Abstract: The pioneering work by Patrick H. O’Farrell established two-dimensional gel electrophoresis as one of the most important high-resolution protein separation techniques of modern biochemistry (Journal of Biological Chemistry 1975, 250, 4007–4021). The application of two-dimensional gel electrophoresis has played a key role in the systematic identification and detailed characterization of the protein constituents of skeletal muscles. Protein changes during myogenesis, muscle maturation, fibre type specification, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 251 publications
(372 reference statements)
0
30
0
Order By: Relevance
“…Briefly, mice (n = 3 animals/group) were euthanized and immediately thereafter brains, spinal cords, thymic and spleens were harvested, washed thoroughly with ice-cold 0.01 M phosphate-buffered saline (PBS, Sigma-Aldrich, St. Louis, MO, USA) containing a protease inhibitor cocktail (4 µM staurosporine, 1 mM α-naphthyl phosphate and 1 mM sodium orthovanadate) to prevent protein degradation during sample preparation and then snap-frozen in liquid nitrogen. Frozen samples were pulverized, solubilized (∼1 µl/1 µg tissue) in pre-chilled lysis buffer (25 mM Tris, 1 mM EDTA, 1 mM EGTA, 150 mM NaCl and 1% Triton x-100) and centrifuged at 125,000 g, 4 • C, for 1 h. Total protein in the supernatant was quantified in each sample using the EZQ protein quantitation kit (Life Technologies, Eugene, OR, USA) with bovine serum albumin (Amresco, Solon, OH, USA) as a calibration standard (Butt and Coorssen, 2005;Churchward et al, 2005). Thymus, spleen, brain, spinal cord and standard purified CD4/8 recombinant proteins (Sino Biological, Wayne, PA, USA) were resolved by 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE; 100 V for 2 h at 4 • C) and then transferred onto polyvinylidene difluoride membrane (PVDF, 0.22 µM pore size, Bio-Rad, Hercules, CA, USA) for 2 h at 4 • C; transfer efficiency, determined as previously described (Sen et al, 2019a), was 95.6 ± 1.7% (Supplementary Figures S1A,B).…”
Section: Western Blotmentioning
confidence: 99%
“…Briefly, mice (n = 3 animals/group) were euthanized and immediately thereafter brains, spinal cords, thymic and spleens were harvested, washed thoroughly with ice-cold 0.01 M phosphate-buffered saline (PBS, Sigma-Aldrich, St. Louis, MO, USA) containing a protease inhibitor cocktail (4 µM staurosporine, 1 mM α-naphthyl phosphate and 1 mM sodium orthovanadate) to prevent protein degradation during sample preparation and then snap-frozen in liquid nitrogen. Frozen samples were pulverized, solubilized (∼1 µl/1 µg tissue) in pre-chilled lysis buffer (25 mM Tris, 1 mM EDTA, 1 mM EGTA, 150 mM NaCl and 1% Triton x-100) and centrifuged at 125,000 g, 4 • C, for 1 h. Total protein in the supernatant was quantified in each sample using the EZQ protein quantitation kit (Life Technologies, Eugene, OR, USA) with bovine serum albumin (Amresco, Solon, OH, USA) as a calibration standard (Butt and Coorssen, 2005;Churchward et al, 2005). Thymus, spleen, brain, spinal cord and standard purified CD4/8 recombinant proteins (Sino Biological, Wayne, PA, USA) were resolved by 10% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE; 100 V for 2 h at 4 • C) and then transferred onto polyvinylidene difluoride membrane (PVDF, 0.22 µM pore size, Bio-Rad, Hercules, CA, USA) for 2 h at 4 • C; transfer efficiency, determined as previously described (Sen et al, 2019a), was 95.6 ± 1.7% (Supplementary Figures S1A,B).…”
Section: Western Blotmentioning
confidence: 99%
“…A comprehensive analysis of the Hela cell proteome by SILAC 2DE‐LC‐LTQ OrbiTrap XL revealed that 676 spots from 816 analyzed ones contained at least two with up to 22 different proteins . Combined with 2DE gel image analysis, conventional 2DE‐based comparative proteomics has been extensively used to determine “differentially expressed proteins” under different physiological, pathological, or pathophysiological conditions as reviewed in the selected publications . However, the protein composition in a human tissue, cell, or body‐fluid proteome is very complex with a very wide abundance range and complicated huge protein speciation caused by splicing, truncation and modification .…”
Section: Introductionmentioning
confidence: 99%
“…2-DGE was initially employed for protein separation and analysis approximately in 1975 [5] . Even though it was introduced more than four decades ago, nowadays 2-DGE is still widely used for whole proteome analysis [6] , [7] , comparative analysis of proteome changes [6] , [8] , biomarker discovery, cancer research [9] , [10] , as well as for the identification of protein isoforms and post-translational modifications [11] , among other purposes. Its popularity could be attributed to several factors.…”
Section: Introductionmentioning
confidence: 99%